2022
DOI: 10.1186/s13059-022-02821-9
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer surveys indicate cell cycle-related roles of primate-specific genes in tumors and embryonic cerebrum

Abstract: Background Despite having been extensively studied, it remains largely unclear why humans bear a particularly high risk of cancer. The antagonistic pleiotropy hypothesis predicts that primate-specific genes (PSGs) tend to promote tumorigenesis, while the molecular atavism hypothesis predicts that PSGs involved in tumors may represent recently derived duplicates of unicellular genes. However, these predictions have not been tested. Results By taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 170 publications
2
9
0
Order By: Relevance
“…We have described individual genes, such as PBOV1 [25,27,29] and ELFN1-AS1 [23,26], and whole classes of tumor-specifically expressed, evolutionarily novel (TSEEN) genes, such as CT antigen genes [28] and ncRNA genes [32,35]. Many of our findings have been confirmed by other authors with references to our priorities [107][108][109][110][111][112][113][114]. In [38], the author suggested considering TSEEN genes as a new superclass of novel and evolving genes with tumor-specific or predominant expression, with several classes and families of TSEEN genes, which includes TSEEN genes of various phyla of organisms.…”
Section: Evolutionarily New and Evolving Genes Should Be Specifically...supporting
confidence: 74%
“…We have described individual genes, such as PBOV1 [25,27,29] and ELFN1-AS1 [23,26], and whole classes of tumor-specifically expressed, evolutionarily novel (TSEEN) genes, such as CT antigen genes [28] and ncRNA genes [32,35]. Many of our findings have been confirmed by other authors with references to our priorities [107][108][109][110][111][112][113][114]. In [38], the author suggested considering TSEEN genes as a new superclass of novel and evolving genes with tumor-specific or predominant expression, with several classes and families of TSEEN genes, which includes TSEEN genes of various phyla of organisms.…”
Section: Evolutionarily New and Evolving Genes Should Be Specifically...supporting
confidence: 74%
“…Mixed UC-MC modules with high Novelty scores also showed a trend of higher expression in tumours and higher prevalence of known driver genes relative to UC-Enriched and MC-Enriched modules. Somatic mutations may act to force the common expression of pairs of unicellular and multicellular genes that would not normally be co-expressed in healthy somatic tissues 16,24 . Amplifications in particular can alter expression of multiple genes simultaneously and thereby rapidly disrupt metazoan GRNs, perhaps explaining their strong enrichment in Mixed UC-MC modules.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work, we found pervasive down-regulation of genes of multicellular origin and selective upregulation of genes of unicellular origin across solid cancers 5,12 , since independently confirmed 13 . Similar approaches showed both genetic and transcriptional alterations accumulate in genes involved in multicellularity during selection for accelerated growth and metastatic potential in breast cancer xenografts 14 , in highly conserved genes in myeloma upon exposure to chemotherapy 15 and in recently-evolved paralogs of cell cycle control genes in cancer cell lines 16 . An example of the functional impacts is the stress-induced activation of error prone, stress-activated DNA repair mechanisms conserved with bacteria in a range of tumours, facilitating drug resistance 17,18 and leaving detectable mutational signatures 19,20 .…”
Section: Introductionmentioning
confidence: 92%
“…The most phylogenetically distant branch at which the shared syntenic block was detected marks the time when a human gene originated. In comparison to the method based on the similarity of protein families, namely the phylostratigraphic dating (Neme and Tautz 2013), this method employed in GenTree is robust to recent gene duplications (Shao et al 2019), despite its under-estimation of the number of young genes (Ma et al 2022). We obtained gene age for human Y genes through the analysis of 15 representative mammals (Cortez et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we found that at least 42% of primate-specific disease genes affecting the nervous systems could impact phenotypes related to brain size and intellectual development. For example, DDX11 is critical in pathology of microcephaly (Pirozzi et al 2018;Lerner et al 2020;van Schie et al 2020;Ma et al 2022). The NOTCH2NLA, NOTCH2NLB, and NOTCH2NLC may promote human brain size enlargement, due to their functions in neuronal intranuclear inclusion disease (NIID), microcephaly, and macrocephaly (Fiddes et al 2018;Suzuki et al 2018;Liu et al 2022).…”
Section: Young Genes Rapidly Acquire Phenotypes Under Both Sexual And...mentioning
confidence: 99%